Negotiating conviviality : the use of information and communication technologies by migrant members of the Bay Community Church - Hay, Paula Louise ([Place of publication not identified] : [publisher not identified], 2014)
This book is an ethnographic study of a group of migrants in Cape Town from Malawi, Zimbabwe and South Africa. It seeks to understand how migrants overcome structural exclusion by forming and maintaining convivial relationships through the Bay Community Church and how this is facilitated by Information and Communication Technologies (ICTs). The book argues that ICTs are implicated in the negotiation of conviviality. ICTs allow for a negotiation of intimacy and distance; although their functions may facilitate more contact than is desired or further distance those already separated physically. This book interrogates the strict division between 'insiders' and 'outsiders' and highlights that migrants are able to sustain multiple networks and relationships, linking their home and host countries. Despite increasingly strict border control and animosity from host communities, migrants are able to overcome imposed identities such as 'outsider'. They do so by using ICTs such as cell phones and Facebook to emphasise their Christian identity, which is one of the main factors for inclusion in church-based networks. Membership with a mixed denominational church such as the Bay further challenges the notion that migrants stick to themselves. Inclusive communities such as the Bay and everyday desires for conviviality evoke the need to reconsider policies too narrowly articulated around the dichotomisation of 'foreigners' and 'nationals', 'home' and 'away', 'us' and 'them'.
Introduction : negotiating intimacy and distance : migration, religion and information communication technology at the Bay Community Church -- Home and away : methods and ethics in the context of multi-spaces fieldwork three -- "Home away from home" : negotiating capital and conviviality at the Bay Community Church -- Inside and outside, intimacy and distance : migrants' use of information and communication technologies in the context of the Bay Community Church. -- Conclusion : a reflection on research findings and multi-spaces anthropological fieldwork references.
Includes bibliographical references (pages 107-123).
Print version record.
Keywords: Bay Community Church (South Africa); Information technology -- Religious aspects -- Christianity; Internal migrants -- Religious life -- South Africa -- Cape Town -- Case studies; Immigrants -- Religious life -- South Africa -- Cape Town -- Case studies; RELIGION -- Comparative Religion; RELIGION -- Essays; RELIGION -- Reference; Information society; Information technology -- Social aspects; Electronic books